Allemagne – la « crise des réfugiés » de l’été 2015. Quelle(s) réponse(s) dans l’album pour la jeunesse germanophone ? - Alexa Craïs; Euriell Gobbé-Mévellec (Strenae)
This article puts forth an analysis of the editorial policy of three German-speaking publishing houses, by studying four children’s picture books, apparently published in conjunction, on the theme of the "refugee crisis" in Germany and Austria in 2015-2016. The investigation concerns the context behind the creation and distribution of the picture books in relation to the textual and iconographic approach of the migration issue as proposed by the authors and illustrators.